Acculturation of Classical, Western Traditions, and Reality: Study of Hassan Hanafi's Thought in Muqaddimah fii 'Ilmi al-Istighrab - Rasid, Ruslan; Djafar, Hilman; Rasyid, Muhammad Rusdi (Universitas Muhammadiyah Magelang, 2021)
Religion must be able to adapt to the environment. Implementing values contained in the scientific realm needs to follow reality and developments. Besides that, it must able to answer all real problems in humanitarian and must be environmental friendly. As a Muslim, what is our attitude towards classical traditions / turats, western civilization and today's reality. This study aims to analyze Hassan Hanafi's thoughts in his Muqaddimah fi ʻilmi istighrab. Hassan Hanafi wants to acculturate the culture of eastern civilization which is termed al-anā with western or European civilization which is termed al-akhār with the aim of eliminating the impact of eurocentrism / eurocentricity (al-Markaziỹah al-Ȗrubiỹah) so that it can balance the flow of western progression and spur the spirit of eastern revival. The method used is the translation method and descriptive analysis. Hassan Hanafi's idea through the concept of al-Istighrāb (oxidentalis) is an effort to acculturate and reject al-Markaziỹah al-Ȗrubiỹah (eurocentrism, eurocentricity) in the sense of stemming European currents that have gone out of their limits because they are considered very influential in the eastern world (Islam).